Optimization of Hypertension and Diabetes Management Through Complementary Therapy - Fitri; Aminah; Eka Yulia Dithah; Fathul Maysarah Syahab; Haekal Tranada Saputra; Ida Diah Pahdila Wahyu Pebiana; Lusmiati; Regita Zsalsabila Rahma; Reza Wira Sanjaya; Selma Aqila Malwani; Siti Nur Rahmadani; Sri Wahyuni; M Bachtiar Safrudin (Journal of Applied Holistic Nursing Science, 2026)
Background: This literature review examines the role of complementary therapy in the management of hypertension and type 2 diabetes mellitus. These two chronic diseases remain major health problems that often require long-term pharmacological therapy with potential side effects. The aim of this study is to identify and analyze various non-pharmacological interventions that can support safe and affordable disease management. Methods: The method used was a systematic review of nine scientific articles published between 2021 and 2025, covering herbal therapy, relaxation, hydrotherapy, and physical exercise on the control of blood glucose levels and blood pressure. Results: The review results indicate that therapies such as warm foot baths, hypertension exercises, butterfly pea tea, garlic infusions, boiled bay leaves (Syzygium polyanthum), moringa leaves (Moringa oleifera), celery leaves (Apium graveolens), diabetes foot exercises, progressive muscle relaxation, and reduced sitting time have been shown to be effective in improving metabolic parameters and patients' quality of life. Conclusion: It can be concluded that complementary therapy is an effective and holistic supportive approach in the care of chronic diseases, but further research with randomized controlled trials (RCTs) is still needed to ensure long-term effectiveness and clinical safety under the supervision of healthcare professionals.